Sodium dodecyl sulfate allows the persistence and recovery of biofilms of Pseudomonas fluorescens formed under different hydrodynamic conditions - Simões, M. (2008)
The effect of the anionic surfactant sodium dodecyl sulfate (SDS) on Pseudomonas fluorescens biofilms was investigated using flow cell reactors with stainless steel substrata, under turbulent (Re=5200) and laminar (Re=2000) flow. Steady-state biofilms were exposed to SDS in single doses (0.5, 1, 3 and 7 mM) and biofilm respiratory activity and mass measured at 0, 3, 7 and 12 h after the SDS application. The effect of SDS on biofilm mechanical stability was assessed using a rotating bioreactor. Whilst high concentrations (7 mM) of SDS promoted significant biofilm inactivation, it did not significantly reduce biofouling. Turbulent and laminar flow-generated biofilms had comparable susceptibility to SDS application. Following SDS exposure, biofilms rapidly recovered over the following 12 h, achieving higher respiratory activity values than before treatment. This phenomenon of posttreatment recovery was more pronounced for turbulent flow-generated biofilms, with an increase in SDS concentration. The mechanical stability of the biofilms increased with surfactant application, except for SDS concentrations near the critical micellar concentration, as measured by biofilm removal due to an increase in external shear stress forces. The data suggest that although SDS exerts antimicrobial action against P. fluorescens biofilms, even if only partial and reversible, it had only limited antifouling efficacy, increasing biofilm mechanical stability at low concentrations and allowing significant and rapid recovery of turbulent flow-generated biofilms.